2009
DOI: 10.1002/adem.200800373
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al‐Containing Interfacial Coatings on Carbon‐Fiber/Bakelite Composite Thermal and Electrical Properties

Abstract: Carbon-fiber polymer-matrix composites are state-of-theart, low-density, high-strength, and high-modulus structural materials. Besides their traditional applications, new fields have emerged, in which, in addition to their good mechanical properties, the electrical and thermal conductivity of these composites are also exploited. New applications include bipolar plates in polymer electrolyte membrane (PEM) fuel cells, [1] thermal management, [2][3][4] and electronic packaging. [5,6] The material properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was observed that 40 CC had the lowest value of CTE (6.93 ppm/°C) than 40 T and 40 SI (9.52 and 10.02 ppm/°C). Previous work stated that thermal expansion indirectly indicated poor adhesion existing between filler and matrix. High thermal expansion indicated poor adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that 40 CC had the lowest value of CTE (6.93 ppm/°C) than 40 T and 40 SI (9.52 and 10.02 ppm/°C). Previous work stated that thermal expansion indirectly indicated poor adhesion existing between filler and matrix. High thermal expansion indicated poor adhesion.…”
Section: Resultsmentioning
confidence: 99%